Combined genome and transcriptome sequencing to investigate the plant cell wall degrading enzyme system in the thermophilic fungus Malbranchea cinnamomea - Hüttner, Silvia; Nguyen, Thanh Thuy; Granchi, Zoraide; Chin-A-Woeng, Thomas; Ahrén, Dag; Larsbrink, Johan; Thanh, Vu Nguyen; Olsson, Lisbeth (Biotechnology for biofuels, 2017)
Genome and transcriptome sequencing has greatly facilitated the understanding of biomass-degrading mechanisms in a number of fungal species. The information obtained enables the investigation and discovery of genes encoding proteins involved in plant cell wall degradation, which are crucial for saccharification of lignocellulosic biomass in second-generation biorefinery applications. The thermophilic fungus is an efficient producer of many industrially relevant enzymes and a detailed analysis of its genomic content will considerably enhance our understanding of its lignocellulolytic system and promote the discovery of novel proteins. The 25-million-base-pair genome of FCH 10.5 was sequenced with 225× coverage. A total of 9437 protein-coding genes were predicted and annotated, among which 301 carbohydrate-active enzyme (CAZyme) domains were found. The putative CAZymes of cover cellulases, hemicellulases, chitinases and pectinases, equipping the fungus with the ability to grow on a wide variety of biomass types. Upregulation of 438 and 150 genes during growth on wheat bran and xylan, respectively, in comparison to growth on glucose was revealed. Among the most highly upregulated CAZymes on xylan were glycoside hydrolase family GH10 and GH11 xylanases, as well as a putative glucuronoyl esterase and a putative lytic polysaccharide monooxygenase (LPMO). AA9-domain-containing proteins were also found to be upregulated on wheat bran, as well as a putative cutinase and a protein harbouring a CBM9 domain. Several genes encoding secreted proteins of unknown function were also more abundant on wheat bran and xylan than on glucose. The comprehensive combined genome and transcriptome analysis of provides a detailed insight into its response to growth on different types of biomass. In addition, the study facilitates the further exploration and exploitation of the repertoire of industrially relevant lignocellulolytic enzymes of this fungus.